1973
DOI: 10.1159/000169617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Left Ventricular Isovolumic Pressure Upon Right Ventricular Pressure Transients

Abstract: Simultaneous, high-fidelity pressure recordings were obtained from the left and right ventricles of anesthetized dogs. Abrupt elevation of left ventricular pressure produced an immediate rise in right ventricular systolic pressure, while mechanical asynchrony of the two ventricles, induced by endocardial pacing of either ventricle, identified discrete pressure transients in the right ventricular pressure pulse which occurred coincident with peak left ventricular dP/dt. During normal conduction, peak right vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
4

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
3
14
0
4
Order By: Relevance
“…The available experimental evidence, supported by the present study, suggests that LV contraction tends to reduce the volumes of both ventricles. [13][14][15][16][17][18][19][20][21][22]31 Isner and Roberts28 were unable to demonstrate a relationship between the extent of human RV free wall infarction at autopsy and the severity of RV dysfunction before death, a finding consistent with results of RV free wall ablation studies in animals. "20 At autopsy, human RV infarction is virtually always associated with infarction of the diaphragmatic surface of the LV and posterior ventricular septum,2830 the infarct distribution resembling an inverted "T.' The frequency of RV dysfunction and RV free wall motion abnormalities associated with inferior infarction appears to be higher than the frequency of either scintigraphic or autopsy evidence of RV infarction, 8 4%48 although reversible ischemia of the RV free wall may explain some of this discrepancy.…”
Section: Discussionmentioning
confidence: 84%
“…The available experimental evidence, supported by the present study, suggests that LV contraction tends to reduce the volumes of both ventricles. [13][14][15][16][17][18][19][20][21][22]31 Isner and Roberts28 were unable to demonstrate a relationship between the extent of human RV free wall infarction at autopsy and the severity of RV dysfunction before death, a finding consistent with results of RV free wall ablation studies in animals. "20 At autopsy, human RV infarction is virtually always associated with infarction of the diaphragmatic surface of the LV and posterior ventricular septum,2830 the infarct distribution resembling an inverted "T.' The frequency of RV dysfunction and RV free wall motion abnormalities associated with inferior infarction appears to be higher than the frequency of either scintigraphic or autopsy evidence of RV infarction, 8 4%48 although reversible ischemia of the RV free wall may explain some of this discrepancy.…”
Section: Discussionmentioning
confidence: 84%
“…The LV can contribute directly to RV contractility via mechanical coupling of the ventricles, inasmuch as continuity of the RV free wall with the LV myocardium permits the transmission of forces generated by LV contraction (7). This is supported by studies showing that 1) surgical replacement of the RV free wall with a prosthetic patch has little effect on RV dP/dt (50,52), 2) alteration of LV free wall function directly affects RV developed pressure (49), and 3) one of the peaks of RV dP/dt coincides with the peak of LV dP/dt (13,14,17,38). In our study, RV dP/dt max was linearly related to A PP in control and RVPO (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Experimental studies have shown that about 20% to 40% of the RV systolic pressure and volume outflow result from LV contraction. 17 Oboler et al in 1973, 18 by recording high-fidelity pressure from the left and right ventricles of anesthetized dogs, demonstrated that the derivative of the RV pressure is composed of the intrinsically generated pressure plus the LV component.…”
Section: Discussionmentioning
confidence: 99%